Exploring Ghanaian Tertiary Students’ Perceptions Towards AI as a First-Hand Source of Health Information for Diagnosis and Self-Medication - Nyarko, Albert Junior (Journal of Health Informatics in Africa, 2024)
Background and Purpose: The rapid advancement of Artificial Intelligence (AI) has opened new avenues in various sectors, including healthcare. In Ghana, where healthcare resources are limited, AI has the potential to bridge the accessibility gap and provide cost-effective health information and services. Therefore, this study aimed to explore Ghanaian tertiary students’ perceptions toward AI-driven health information platforms. The study’s objectives align with the broader impact of AI-driven health information platforms, emphasizing the need to assess awareness, trust, factors influencing willingness to use AI, and potential concerns among Ghanaian tertiary students. Methods: The study employed a cross-sectional survey design to gather quantitative data from 50 Ghanaian tertiary students using structured questionnaires. Open-ended responses related to concerns and reservations regarding AI as a health information source were analyzed using thematic analysis. Themes and patterns were identified. Results: The findings revealed that approximately 56% of respondents knew of AI-driven health platforms, with "Ada" being the most recognized. Trust in AI-based health information varied based on age and gender, with young females exhibiting the highest trust. Factors influencing willingness to use AI included perceived usefulness, perceived ease of use, positive prior experiences, and technological literacy. Conclusions: The study recommends educational campaigns, enhancing trust, user-friendly platforms, academic integration of AI education, and addressing ethical considerations to promote AI adoption in healthcare decision-making among Ghanaian tertiary students. These insights can inform policymakers and healthcare providers in developing effective strategies to harness AI’s transformative potential in healthcare accessibility in Ghana. Keywords: Artificial Intelligence, healthcare delivery, Ada, Technology Acceptance Model (TAM), Ghana